Application in the analysis of the occlusal force of free-end missing tooth implant restoration with T-SCAN III - Wu, Ming-Le; Lai, Peng-Yu; Cheong, Fan; Zhou, Wen-Cheng; Xu, Sang-Hui; Li, Hui; Shen, Shan (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: The occlusal force of the teeth in the dental arch and the remaining adjacent natural teeth will change after implant restoration with a free-end missing tooth. This study intends to use the T-SCAN III scanner to collect dynamic quantitative data before and after the restoration of free-end implants and to explore the application of the T-SCAN III in redistributing the occlusal force of free-end implants. Methods: In this study, 24 patients with free-end implant restoration were selected, and their occlusion was tested before, immediately after, and three months after implant restoration. Results: In all 24 cases, the bite force of the first natural tooth adjacent to the implanted tooth after restoration changed from 19.12% ± 9.48% to 12.93% ± 11.47% (P < 0.01). For additional data analysis, all cases were further subdivided by single implant and fixed bridge restorations. In 17 cases, there was a successful follow-up after three months. The percentage of the total bite force of dental arch with implant increased from 41.92% ± 10.78% to 53.06% ± 10.71% (P < 0.01). Conclusion: This study shows that the free-end implant restoration protects the remaining natural teeth, and the patient's missing dental arch bite force improves within three months of implant restoration.